Improving machines for production of fuel material of necessary fraction for household use - Ляшенко, С. В.; Пошивайло, Ю. О. (Scientific Progress & Innovations, 2017)
The use of fuel material in the conditions of a personal peasant economy is considered. An analysis of the effectiveness of different types of biofuels is carried out. The expediency of using wood chips as an alternative to biofuel is substantiated. The analysis of constructions of industrial machines for making of wood chips is presented. It is established that for designing a household chipper its construction should be provided disk-knife working element and calibration sieve.